2015
DOI: 10.1177/0193841x15570046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Higher Education Policy Frameworks for Open and Distance Education in Pakistan

Abstract: The distance education program initiative in Pakistan is of promising nature which needs to be assessed regularly. This study has made an initial attempt to assess the policy document against a criterion identified from literature. The analysis shows that the current policy documents do offer some strengths at this initial level, however, they cannot be considered a comprehensive policy guide. The inclusion or correction of missing or vague areas identified in this study would make this policy guideline docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In the study of Barimani et al, 27 reviewing policy in higher education based on knowledge market requirements, adapting curricula to the needs of society and industry and paying more attention to the social responsibility of the university, and providing educational and motivational programs for professors, students and staff and university administrators concerning the requirements of globalization and the components of the knowledge market and their empowerment are necessary, which is consistent with the results obtained in terms of updating resources and information. The results of this study are in line with the model of Ellahi and Zaka, 28 in terms of prioritizing social interests in strategies for evaluating medical education policies, which refers to public opportunities (stakeholder participation) in the evaluation model of the higher education policy framework. "Variety of educational programs", "Inclusive", and "Creating equal and continuous learning opportunities" in Kamyabi et al 29 were identified as some of the basic policies of medical education that need to be reviewed, and this finding is consistent with the results of the current study with a precise definition and design of policies that executive policies are part of the strategies related to the evaluation of medical education policies.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…In the study of Barimani et al, 27 reviewing policy in higher education based on knowledge market requirements, adapting curricula to the needs of society and industry and paying more attention to the social responsibility of the university, and providing educational and motivational programs for professors, students and staff and university administrators concerning the requirements of globalization and the components of the knowledge market and their empowerment are necessary, which is consistent with the results obtained in terms of updating resources and information. The results of this study are in line with the model of Ellahi and Zaka, 28 in terms of prioritizing social interests in strategies for evaluating medical education policies, which refers to public opportunities (stakeholder participation) in the evaluation model of the higher education policy framework. "Variety of educational programs", "Inclusive", and "Creating equal and continuous learning opportunities" in Kamyabi et al 29 were identified as some of the basic policies of medical education that need to be reviewed, and this finding is consistent with the results of the current study with a precise definition and design of policies that executive policies are part of the strategies related to the evaluation of medical education policies.…”
supporting
confidence: 82%
“…The strategies obtained from the qualitative research were provided to the respondents through a questionnaire, and the results of the first and second-order confirmatory factor analysis are as follows: Nine strategies and 61 items were used in the research factor analysis to examine the strategies related to the evaluation of medical education policies. Strategies for simultaneous attention to institutional and non-institutional agenda were examined with questions (1-6); Prioritizing social interests were examined with questions (7-10); Economic strategies were examined with questions (11)(12)(13)(14)(15)(16); Updating resources and information were examined with questions (17)(18)(19)(20)(21); Precise definition and design of policies were examined with questions (22)(23)(24)(25)(26)(27)(28); Executive strategies were examined with questions (29-37); Systematic policy was examined with questions (38-44); Monitoring and evaluation strategies were examined with questions (45-52); Policy research was examined with questions (53-61). The criterion for validating factors and items related to each factor in the confirmatory factor analysis is that the amount of factor load is above 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…As a respect of their ancestor values, the family preferred to maintain the Teacher-Student relationship. The rising demand of MOOCs challenge the educational organization includes university and government to create a formal and comprehensive regulation and policy [45]. The students of MOOCs must get assurance regarding the quality of the course offered.…”
Section: Resultsmentioning
confidence: 99%
“…Academic exchanges with international scholars contribute to the expansion of international networks, which can be beneficial to the local institutions (Bremer, 2018). Through international exchange programs, students are offered the opportunity to experience studying in a multicultural environment that in turn leads to an enhancement of their psychological and sociocultural adaptation skills (Ellahi & Zaka, 2015; Larbi & Fu, 2017; Forstorp, 2017; Abdulai, Roosalu & Wagoner, 2021). The increase in publications of scholarly journals not only enhances the production of knowledge but also improves the academic reputation of institutions and staff (Abramo, D’Angelo & Di Costa, 2009).…”
Section: Internationalization In Universitiesmentioning
confidence: 99%